The Influence of Copywriting Training on Soft Skill Development to the National Senior High School Students of Bandung City - Rizky Ilhami; M Rizky Ganda Hutama; Mahesa Heryanto; Kintan Gandari (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of copywriting training on the development of soft skills in students of SMA Nasional Bandung City. Soft skills are important competencies that students need to have, including communication skills, creativity, and critical thinking. This study uses a quantitative approach with an experimental research design and multiple linear regression analysis. Data were collected from 100 students who participated in copywriting training, with independent variables being student motivation, copywriting training, and creativity. The results of the analysis show that copywriting training has a positive and significant effect on the development of students' soft skills (p-value = 0.015). Creativity also has a very significant effect with a very small p-value (0.000), while student motivation does not have a significant effect on the development of soft skills (p-value = 0.195). The regression model used has an R Square value of 0.980, which means that 98% of the variation in soft skill development can be explained by the variables tested. This study concludes that copywriting and creativity training play an important role in improving students' soft skills, while student motivation does not show a significant effect in this model.